2009
DOI: 10.1143/apex.2.075501
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Highly Crystalline Corundum-Structured α-(Ga1-xFex)2O3Alloy Thin Films on Sapphire Substrates

Abstract: Highly crystalline corundum-structured -(Ga 1Àx Fe x ) 2 O 3 alloy thin films were fabricated on c-plane sapphire substrates by using a mist chemical vapor deposition method. The full-widths at half maximum of X-ray diffraction rocking curves were smaller than 100 arcsec for the entire range of x from 0 to 1. Optical band gaps were artificially tuned to a value between those of -Ga 2 O 3 and -Fe 2 O 3 , that is, 2.2 and 5.3 eV with changing the Fe content x in the films. Magnetic measurements revealed ferromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 28 publications
(33 reference statements)
3
73
0
1
Order By: Relevance
“…It is interesting to note that lattice parameters (a and c) and cell volume (V) of the samples (shown in Table I) have increased slowly up to the milling time 100 hours, despite the fact that radius of Ga 3+ (0.62 Å) is smaller than Fe 3+ (0.67 Å). 6 Similar lattice expansion with decreasing grain size was observed in mechanical milled α-Fe 2 O 3 . 35 The increase of cell parameters in milled samples with milling time up to 100 hours is primarily due to the effect of better alloying of two binary oxides (α-Ga 2 O 3 and α-Fe 2 O 3 ) to attain the structure of α-Fe 2 O 3 phase with higher cell parameters (a = b= 5.0386 Å, c = 13.7498 Å, V = 302.3 Å 3 ).…”
Section: Methodssupporting
confidence: 58%
See 2 more Smart Citations
“…It is interesting to note that lattice parameters (a and c) and cell volume (V) of the samples (shown in Table I) have increased slowly up to the milling time 100 hours, despite the fact that radius of Ga 3+ (0.62 Å) is smaller than Fe 3+ (0.67 Å). 6 Similar lattice expansion with decreasing grain size was observed in mechanical milled α-Fe 2 O 3 . 35 The increase of cell parameters in milled samples with milling time up to 100 hours is primarily due to the effect of better alloying of two binary oxides (α-Ga 2 O 3 and α-Fe 2 O 3 ) to attain the structure of α-Fe 2 O 3 phase with higher cell parameters (a = b= 5.0386 Å, c = 13.7498 Å, V = 302.3 Å 3 ).…”
Section: Methodssupporting
confidence: 58%
“…In the octahedral environment of ( Fig. 6(a)) at ∼860 nm, ∼630 nm, ∼540 nm, ∼340 nm are corresponding to 6 44 We have found that high intense absorption band (at about 600), as well as other absorption peaks are shifting towards higher wavelength side (Fig. 6(b)) with the increase of milling time of Ga doped α-Fe 2 O 3 compound.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Gallium oxide is a wide-band-gap semiconductor with important applications in transparent conductive oxides, 1 deep ultraviolet solar-blind detectors, 2,3 spintronics, 4 high temperature gas sensors, 5 and novel functional oxides. 6 The monoclinic b-phase is thermodynamically the most stable phase at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of alloying with a-Fe 2 O 3 and a-Cr 2 O 3 opens up the possibility of harnessing multiferroic and magnetoelectric effects. 4,13 On the other hand, the a-Ga 2 O 3 has a moderate in-plane a-lattice parameter misfit ($4.8%) 14 with a-Al 2 O 3 and a substantially lower bandgap ($5 eV for a-Ga 2 O 3 ) 15,16 compared to sapphire. This makes the a-Ga 2 O 3 /a-Al 2 O 3 system an interesting possibility for the development of intersubband devices operating at telecommunication wavelengths.…”
Section: Introductionmentioning
confidence: 99%